2018
DOI: 10.5664/jcsm.6900
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure in Patients With Obstructive Sleep Apnea and Non-Alcoholic Steatohepatitis: A Systematic Review and Meta-Analysis

Abstract: PROSPERO; ID: CRD42015027981; URL: https://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42015027981.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…However, the available studies have yielded mixed results and are listed in Table 2 and Table 3. 80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] In these studies, the impact of CPAP therapy on NAFLD was assessed by means of improvements in liver enzymes, hepatic adiposity, or fibrosis. Importantly, the observational studies that demonstrated the benefits of CPAP (see Table 2) were of longer duration than the randomized controlled trials that did not show CPAP to be beneficial (see Table 3).…”
Section: Obstructive Sleep Apnea and Liver Fibrosismentioning
confidence: 99%
“…However, the available studies have yielded mixed results and are listed in Table 2 and Table 3. 80,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] In these studies, the impact of CPAP therapy on NAFLD was assessed by means of improvements in liver enzymes, hepatic adiposity, or fibrosis. Importantly, the observational studies that demonstrated the benefits of CPAP (see Table 2) were of longer duration than the randomized controlled trials that did not show CPAP to be beneficial (see Table 3).…”
Section: Obstructive Sleep Apnea and Liver Fibrosismentioning
confidence: 99%
“…However, the duration of CPAP treatment was less than two months in these trials, so the authors concluded that the lack of favorable results was probably due to the short treatment course. Finally, another recent meta-analysis confirmed these findings, showing no difference in improvement of liver steatosis and markers of liver injury after CPAP treatment [118].…”
Section: Resultsmentioning
confidence: 75%
“…Improvement in hepatic disease also improves renal function [90]. Obstructive Sleep ApneaOSA is significantly associated with more “severe” forms of NAFLD and the treatment of OSA with CPAP therapy seems to improve the liver injury [103,104,110,111,112,113,114,115,116,117,118,119]. EndocrinopathiesPolycystic ovarian syndromeHypothyroidismObesity and IR are common risk factors for both PCOS and NAFLD [207,208,209,210].…”
Section: Table A1mentioning
confidence: 99%
“…Continuous positive airway pressure (CPAP) is considered the gold standard treatment with OSA patient, and this treatment is marginally effective in reducing elevated arterial pressure (~2 mmHg), and sympathetic nerve activity and partially restoring chemoreflex and baroreflex sensitivity [ 14 , 15 ]. However, the use of CPAP was not associated with reduced risks of cardiovascular outcomes, diabetes mellitus, or death for patients with OSA in recent randomized controlled trials [ 16 , 17 , 18 ]. Therefore, it is essential to develop novel pharmacological agents to counteract the pathophysiological mechanisms responsible for OSA-related adverse consequences, namely oxidative stress, sympathetic activation, and low-grade inflammation [ 16 ].…”
Section: Sleep Apnea and Metabolic Dysfunctionmentioning
confidence: 99%